Kemampuan Filter Alami Berbasis Kulit Pisang (Musa paradisiaca L.) dalam Penjernihan Air - Sihite, Nadia Okta Kristiana; Sutarno, Sutarno; Parlindungan, Deni; Johan, Henny; Karyadi, Bhakti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Waste from male banana peels (Musa paradisiaca Var. Paradisiaca), Ambon banana peels (Musa paradisiaca Var. Sapientum), and kepok banana peels (Musa acuminate L.) can be used as natural water filtration. The content of pectin, galacturonic acid and cellulose in banana peels can absorb heavy metals in water. This research aims to determine the filtration ability of natural waste materials such as kepok banana peels, Ambon banana peels and male banana peels which are most effectively used as water filtration media. This research consists of the sample preparation stage, carbonization stage, activation stage, and trial stage. The method used is an experimental method on a laboratory scale to measure Potential Hydrogen (pH), Total Dissolve Solid (TDS), and the level of clarity in water. The data obtained was tested using the Anova test with a significance level of 5% and the BNT test. Based on the BNT test which shows that male banana peels are not significantly proportional to the TDS of well water. Meanwhile, Ambon banana peel and Kepok banana peel are significantly proportional to TDS, and for Kepok banana peel, Ambon banana peel and male banana peel, it is significantly proportional to the pH of well water, because the significance results are less than 0.05%. From these findings it can be concluded that Kepok banana peels and Ambon banana peels are the most effective water filtration media to use.